The relationship between grit and L2 willingness to communicate among Chinese undergraduate students: the contributions of foreign language enjoyment and anxiety - Gengchun Li (Humanities & Social Sciences Communications)
Abstract Despite having received more than a decade of English education, many Chinese undergraduate students still face the problem of acquiring communicative competence in English. It has been convincingly argued that the willingness to communicate (WTC) in a second language (L2) is one of the determinants of one’s communicative competence in that language. Therefore, in recent years, the WTC among L2 learners across different cultural and educational contexts has attracted increasing attention from the academic community. A variety of motivational, emotional, and situational factors have been scrutinized for their direct and indirect effects on L2 WTC. However, the personality factor of grit in shaping L2 WTC has been insufficiently investigated, and the possible mediating effects of L2 emotions (e.g., foreign language enjoyment and anxiety) have been relatively under-explored. Based on a sample of 820 Chinese undergraduate English majors, this study investigated the influence of the two dimensions of grit, i.e., perseverance of effort (PE) and consistency of interest (CI), on two types of L2 WTC, i.e., meaning-focused and form-focused L2 WTC; and explored the possible mediating effects of foreign language anxiety (FLA) and three sources of foreign language enjoyment (i.e., FLE-private, FLE-atmosphere, and FLE-teacher) in their relationship. It was found that: (1) PE significantly positively predicted meaning-focused and form-focused L2 WTC; (2) FLE-private, FLE-atmosphere, and FLA partially mediated the relationship between PE and meaning-focused/form-focused L2 WTC; (3) FLA exerted a masking effect in the relationship between CI and meaning-focused L2 WTC, while fully mediating the relationship between CI and form-focused L2 WTC. The results of this study can provide implications for the cultivation of L2 WTC among Chinese undergraduate English majors.